Systemic Risk and Financial Consolidation : Are they Related? - De Nicolo, Gianni; Kwast, Myron (Washington, D.C. : International Monetary Fund, 2002)
We argue that firm interdependencies, as measured by correlations of stock returns, provide an indicator of systemic risk potential. We find a positive trend in stock return correlations net of diversification effects for a sample of U.S. Large and Complex Banking Organizations over 1988-99. This finding suggests that the systemic risk potential in the financial sector may have increased. In addition, we find a positive consolidation elasticity of correlations. However, such elasticity exhibits substantial time variation and likely declined in the latter part of the decade. Thus, factors other than consolidation have also been responsible for the upward trend in return correlations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet